2003
DOI: 10.1081/ddc-120021777
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dissolution Profiles for Albendazole Tablets Using USP Apparatus 2 and 4

Abstract: The in vitro dissolution of albendazole from three different commercially available products (200 mg tablets) was studied using U.S. Pharmacopeia (USP) Apparatus 2 and USP Apparatus 4 in order to compare the release performance of the drug in two essentially different dissolution systems. For both cases, 0.1 N HCl was used as dissolution medium. Only the reference product and one of the generic products studied met the 80% USP 24 specification for albendazole dissolved at 30 min, using USP Apparatus 2. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…2 clarified that USP apparatus IV was the dissolution apparatus that revealed the highest sensitivity and discriminative capability in differentiating between the dissolution behavior of MH products than USP apparatus II and beaker method. Similar observations were reported by Hurtado y de la Peña et al [43] who highlighted by statistical analysis the discriminative capability of USP apparatus IV versus USP apparatus II in differentiating the release characteristics of tested albendazole products. Fig.…”
Section: Usp Apparatus IVsupporting
confidence: 88%
See 1 more Smart Citation
“…2 clarified that USP apparatus IV was the dissolution apparatus that revealed the highest sensitivity and discriminative capability in differentiating between the dissolution behavior of MH products than USP apparatus II and beaker method. Similar observations were reported by Hurtado y de la Peña et al [43] who highlighted by statistical analysis the discriminative capability of USP apparatus IV versus USP apparatus II in differentiating the release characteristics of tested albendazole products. Fig.…”
Section: Usp Apparatus IVsupporting
confidence: 88%
“…Likewise, other researchers faced such out of limits results. For example, Hurtado y de la Peña et al [43] reported that for different marketed albendazole products, only the reference product and one of the generic products studied met the USP specifications. Moreover, Emara et al [18] presented two commercial products of gliclazide that failed to meet the requirements described by the British Pharmacopoeia.…”
Section: Beaker Methodsmentioning
confidence: 99%
“…Dissolution rates from a flow-through apparatus have previously been investigated in relation to flow rates (1)(2)(3)(4)(5)(6)(7)(8)(9). Comparisons have also been made between dissolution rates in the paddle apparatus and the flow-through apparatus (3,7,8,10). Suggested flow rates in the flow-through dissolution apparatus (USP apparatus 4 (Flow-Through Cell)) are 4 to 16 ml min −1 (11), although higher flow rates can be, and have been, used (4).…”
Section: Introductionmentioning
confidence: 99%
“…Working with an unlimited amount of solvent is possible, thus overcoming problems due to nonsink conditions. 4. pH changes may be easily performed stepwise since the medium is exchanged very rapidly in the low volume cells (this allows adaptation of test parameters to physiological conditions).…”
mentioning
confidence: 99%
“…USP Apparatus 4 has been useful in developing more discriminative dissolution methods than those that employ apparatus 1 or 2, as was demonstrated with commercial tablets of albendazole and carbamazepine, both having low solubility (4,5). Despite the advantages of apparatus 4 over the basket and paddle equipment, little information is available on its application in the evaluation of generic drug products with solubility problems.…”
mentioning
confidence: 99%